CFD Simulations of Snowdrifts on a Gable Roof: Impacts of Wind Velocity and Snowfall Intensity - Guolong Zhang; Yu Zhang; Ziang Yin; Qingwen Zhang; Huamei Mo; Jinzhi Wu; Feng Fan (Buildings, 2022)
Roof structures are suffering serious threats caused by unbalanced snow distribution, especially long-span spatial structures, such as gable roofs. The formation of unbalanced snowdrifts on the gable roof is affected by the meteorological condition and the drifting snow. This study was conducted to explore the snowdrift characteristics on gable roofs under different snowfall conditions based on a new Eulerian–Eulerian multiphase approach. To consider the diffusive process of snow in different states, the governing equations of air and snow phases were modified separately according to the actual transport process. Additional terms based on the deposition/erosion process were inserted into the governing equations to consider the processes of snow particles being trapped or ejected by snow surface. The feasibility of the new model for the snowdrift was validated by comparing with a field observation. Then, the snowdrifts characteristics on typical gable roofs were investigated under different wind velocity and snowfall intensity conditions. The formation mechanism of snowdrifts and the influence of meteorological conditions on snowdrifts were clarified by analysis. The results show that the uneven distribution of snow on the gable roof becomes more significant with the increase in wind velocity. Furthermore, the distribution of snow on the roof tends to be more even in the case of heavier snowfall.